Seeing is Believing. Anthropological Visions of Culture - Drozdowicz, Jarema (Wydawnictwo Naukowe Uniwersytetu im.Adama Mickiewicza w Poznaniu, 2013)
The main argument of the article tends towards the assumption that the visual sphere of culture is one of the most significant features of human agency and it is closely connected to the process of constructing particular worldviews. The scientific discourse that follows the issue of visuality has therefore a long history of transitions and paradigm shifts, just like the cultural discourse in general. Cultural anthropology developed with the passing time also its own way of seeing things, especially when it comes to the conceptualization if cultural otherness. Visual anthropology, understood as an independent anthropological field of study, gained with time much recognition amongst other social sciences, being part of a much broader visual turn in the social sciences. What is significant the contemporary image discourse shifts its momentum towards the „native’s point of view”, i.e. it recaptures the reality in terms of subjective and culturally conditioned ways of percepting the world.
Zobaczyć znaczy uwierzyć. Antropologiczne spojrzenia na kulturę
Keywords: visual anthropology; visual turn; culture; history of image; de-visualization discourse